Influence of surface processes on post-rift faulting during divergent margins evolution - Silva, Rafael Monteiro da (2021)
The evolution of divergent continental margins depends on the interaction between the Earth\'s interior dynamics and the surface processes of erosion and sedimentation. Due to the complexity of the different processes involved in extensional settings, the use of numerical models is a natural tool to study the development of these margins. In the last decade, different numerical models were developed to simulate the interplay between surface and tectonic processes, mainly focusing on the sin-rift evolution of divergent margins, evaluating how erosion and sedimentation can affect the thermal and stress states of the crust and mantle during lithospheric stretching. However, from the point of view of the numerical modelling community, little attention has been paid to the post-rift evolution of divergent margins, tens of millions of years after the continental breakup. Therefore, the aim of the present work is the development and application of thermo-mechanical numerical models that simulate the formation and evolution of divergent continental margins since continental rifting, taking into account surface processes of erosion and/or sedimentation, running the numerical experiments for a time-span of 50-100 million of years. Based on two independent numerical models presented in this thesis, I conclude that the degree of coupling between the upper crust and the lithospheric mantle, the magnitude and extent of erosion of the coastal landscape, and the preexistence of weakness zones in the continental crust are important elements that control the reactivation of faults along divergent margins during the post-rift phase. The numerical experiments indicate that the presence of a lower crust with a relatively low viscosity, facilitating the decoupling of the upper crust and the development of hyper-extended margins, can also contribute to the development and/or reactivation of normal faults in the interior of the continent when the margin is continually subjected to differential denudation. This effect is suppressed in scenarios where the lower crust presents a relatively high viscosity, consequently inducing the coupling of the upper crust with the lithospheric mantle. In this case, the long wavelength of the flexural response of a coupled lithosphere to erosional unloading has a minor impact on the reactivation of faults in the upper crust. Additionally, the preexistence of weak zones in the upper crust, e.g. due to a low internal cohesion of the rocks, can contribute to nucleate normal faults, amplifying the strain rate in these regions during phases of high denudation rates. These conclusions are applied to study the post-rift evolution of the southeastern Brazilian margin, where a Cenozoic tectonism created the Continental Rift of Southeastern Brazil (CRSB). I propose that the combination of a decoupled continental lithosphere and the preexistence of shear zones parallel to the coast contributed to development of the CRSB. Furthermore, the magnitude of post-rift denudation along the Southeastern Brazilian margin, between 3 to 4 km as indicated by thermochronological data, amplified the flexural rebound and favoured the extensional regime in the upper crust, mainly in the hinterland.